Vision Impairment and Eye Care Utilization among Americans 50 and Older - McGwin, Gerald (2010)
BACKGROUND: Few studies have provided population-based estimates of the vision impairment, eye disease and eye care in the United States. Using data from the Behavioral Risk Factor Surveillance System (BRFSS) this study reports the overall and age-race-specific prevalence of self-reported vision impairment, eye diseases, and eye care utilization among older adults. METHODS: Between 2005 and 2008 residents aged 50 and older in seventeen states responded to BRFSS questions concerning difficulty with distance and near vision-related tasks, self-reported eye diseases and reported eye care insurance and service utilization. RESULTS: The overall prevalence of difficulty with distance and near vision was 16.6% and 32.8%, respectively with no meaningful change with increasing age. The prevalence of cataract, glaucoma, and macular degeneration was 19.6%, 6.4%, and 5.8%; all of which increased dramatically with age. Nearly 69% of Whites and Blacks and 65% of Hispanics visited an eye care provider in the past year. Overall, among the approximately one-third of participants who did not visit an eye care provider in the past year, half indicated that they did not have any reason to go and 20% cited it was due to cost/insurance. CONCLUSION: The continued and expanding use of the BRFSS Visual Impairment and Access to Eye Care module represents a unique opportunity to obtain population-based estimates of vision impairment, eye disease and, perhaps most uniquely, eye care utilization. Moreover, the integration of this and other BRFSS modules will provide researchers the opportunity to evaluate the relationship between these estimates and other measures of health status and health care utilization. However, the self-reported nature of the BRFSS data is an important limitation that must be considered when interpreting the results.